ALGINATE IMPRESSION VS ALGINATE IMPRESSION PLUS CASSAVA STARCH: ANALISIS GAMBARAN MIKROSKOPIK - Febriani, Mirna (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2011)
Backgrounds. Alginate impression material is a material to make impression of teeth and oral cavity. Theresult will be reproduced by gypsum type III. Alginate impression material can modify with cassava starch with ratio 1:1.The major composition is algin or alginat acid and cassava starch composition are amylose 25 % andamylopectine 75 %. Material and methods. Alginate impression type normal setting, cassava starch, aquadestilata,light microscope and polarization microscope. Result. Microscopic structure alginate impression with light microscope showed that birefringence structure less than birefringence structure alginate impression with cassaca starch. When the structure is changed, the crystallite of cassava starch will be changed. Conclusions. The added cassava starch to alginate impression microscopically will not form a new chemical compound, will not change the molecule structure of alginate impression, without any chemical reaction between alginate impression with cassava starch and only produce the physical bond.